Modulation of the nutritional and functional values of common bean by farming system: organic vs. conventional - Rodríguez Madrera, Roberto; Campa Negrillo, Ana; Ferreira Fernández, Juan José (Frontiers in Sustainable Food Systems, 2024)
Common bean (Phaseolus vulgaris L.) is a crop of high nutritional interest which is widespread throughout the world as a result of which it is considered as a potential crop for ensuring future food security. The effect of organic and conventional farming systems on the nutritional and functional composition of two cultivars of market class fabada (a landrace and a modern elite cultivar) is described. The findings of our study have shown that the common beans from organic farming have a higher content of protein, phenolic compounds, and relevant microelements such as iron and zinc than the seeds from conventional farming trial. However, in conventional crops a higher content of polyunsaturated fatty acids and lower concentrations of phytic acid and raffinose oligosaccharides were also detected. In contrast, no significant differences were detected in the proximate composition of the two genotypes tested, nor in their antioxidant activity or levels of phenolic compounds. The elite cultivar maintains the nutritional characteristics of the landrace from which it derives, suggesting the genomic regions modified in the improvement do not play an important role in their genetic control.